Short Communication: Community structure and diversity of Odonata in Suranadi Natural Park, West Lombok Indonesia - MOHAMMAD LIWA ILHAMDI; AGIL AL IDRUS; DIDIK SANTOSO; Gito Hadiprayitno (Society for Indonesian Biodiversity, 2020)
Abstract. Ilhamdi ML, Al Idrus A, Santoso D, Hadiprayitno G. 2020. Short Communication: Community structure and diversity of Odonata in Suranadi Natural Park, West Lombok Indonesia. Biodiversitas 21: 718-723. Odonata is an order of insects. The life cycle of this order is dependent on freshwater habitat. Sensitivity to environmental changes causes odonates to be important bioindicators of ecosystem change. The importance of the ecological role of odonates is not followed by adequate scientific information on Odonata communities, especially in the Suranadi Natural Park (SNP). The study aimed to monitor the existence and community structure of Odonata in the SNP area every six months in period. The data collection technique was using a survey method by following the transect line, namely the waterway transect line (WTL), plantation border transect (PT) and settlement border transect (ST). Data collection was done 4 times from April to May 2019, once every 2 weeks. The sampling was done twice in the morning from 08.00 to 11.00 AM and in the afternoon from 03.00 to 05.00 PM. Data were analyzed using the relative frequency equation and Diversity Index. The results showed that there were 16 species of odonates consisting of the family Libellulidae (11 species), Platycnemididae (1 species), Chlorocyphidae (1 species), and Coegrinidae (3 species). Orthetrum sabina, Neurothemis ramburii, Diplacodes trivialis, Gynacantha subinterrupta, Copera marginipes, and Pantala flavescens, are species that are present in all of each observation sites. The waterway transect has the highest diversity index (2.027), followed by settlement transect (1.367), and the lowest is plantation transect (1.131).